Adiponectin and the steatosis marker Chi3L1 decrease following switch to raltegravir compared to continued PI/NNRTI-based antiretroviral therapy. - Obiageli Offor (PLoS ONE, 2018)
People with HIV are at for metabolic syndrome (MetS) and fatty liver disease, but the role of Antiretroviral therapy (ART) is poorly understood. MetS and fatty liver disease been associated with changes in adiponectin, soluble ST2 (sST2), chitinase 3-like 1 (Chi3L1), hyaluronic acid (HA), tissue inhibitor of metalloproteinase-1 (TIMP-1), lysyl oxidase-like-2 (LOXL2) and transforming growth factor β (TGF-β) concentrations in HIV-uninfected populations. Protease (PI) and non-nucleoside reverse transcriptase inhibitors (NNRTI) may contribute to these comorbidities, but the effects of switching from PI- or NNRTI to raltegravir (RAL) on these biomarkers is unknown.Cryopreserved plasma was obtained from a completed, prospective trial of HIV-infected women with central adiposity on NNRTI- or PI-based ART during which they were randomized to remain on their current ART or switch to a RAL based regimen. Biomarker concentrations were quantified using ELISA and Multiplex assays at baseline and 24 weeks after randomization. Wilcoxon-signed rank test evaluated within-group changes, Spearman and linear regression models evaluated correlations between biomarkers and clinical covariates.Participants had a median age of 43 years, CD4+ T lymphocyte count 558 cells/mm3 and BMI 32 kg/m2; 35% met criteria for MetS. At baseline, higher adiponectin levels correlated with higher Chi3L1 levels (r = 0.42, p = 0.02), as did declines after 24 weeks (r = 0.40, p = 0.03). Changes in sST2 correlated with changes in Chi3L1 (r = 0.43, p = 0.02) and adiponectin (r = 0.40, p = 0.03). Adiponectin and Chi3L1 levels decreased significantly in women switched to RAL vs continue PI/NNRTI.In women with HIV and central obesity, the hepatic steatosis/fibrosis marker Chi3L1 and adiponectin decrease in conjunction with sST2 decreases following switch to RAL. Whether switching from NNRTI/PI-based regimens to RAL can improve hepatic steatosis and dysmetabolism requires further study.Clinicaltrials.gov NCT00656175.